Teachers opinions, beliefs and attitudes regarding accidents and their prevention. (1st March 2011) - Ungaro, J F; De Hoyos, G H; Enders, J
Abstract : Objectives: (1) to describe the opinions and beliefs among teachers of educational units in Argentina regarding (a) injuries as a health problem; b) Accidents characteristics, their prevention and causal attribution c) Schools` role in the prevention (2) to explore their attitudes regarding the feasibility the school involvement in prevention programs. Material and methods: Data was collected through self-administered questionnaires. 322 educational units took part of the study and 3752 completed questionnaires were obtained. Answer categories were defined by contents analysis. Factorial analysis of multiple correspondences and mixed classification were then carried out. From these results a second survey was designed and administered to 2100 teachers from 350 schools. A typology of their answers was obtained from a new multidimensional analysis. The typical expressions of each class were identified by contents analyses. Results: Only a small minority (2%) of the participants identifies injuries as a problem. According to their opinions and beliefs, four different groups according to their opinions and beliefs were identified: (1) those who agree that accidents are preventable events; (2) those who see them as unpreventable situations given sociocultural factors; (3) those who sustain a deterministic conception; and (4) those who support a fortuitous, casual view. Discussion and Conclusions: Ignorance regarding the problems magnitude and teachers` beliefs and opinions about accidents nature could endanger education effectiveness and preventive programs success. A deep analysis of the problem by educational staff is required in order to change attitudes.